Kasem Bundit University : Pursuing transparency and collective anti-corruption efforts - Suwandee, Senee; Rattanamaneichatr, Chiratus; Chaokromthong, Kajohnsak; Jarougjareet, Agkrawit; Sukjaroen, Nitibodee (KASEM BUNDIT JOURNAL, 2025)
PURPOSES: To promote and instill integrity, enhance knowledge and skills, and establish collaborative networks for preventing and combating corruption based on the STRONG Model among students, faculty, and staff to foster transparency and sustainability. METHODS: A quantitative approach to evaluate the project “Kasem Bundit University: Pursuing trans parency and collective anti-corruption efforts. The project consisted of five components, namely Digital Anti-Corruption Challenge, STRONG Innovation Workshop, STRONG: Sufficient Mind Against Corruption course, STRONG Student Leaders Network, and Future University Anti-Corruption Forum. The target group totaled 510 participants. Questionnaires were used for data collection. Data from pre- and post-tests and satisfaction surveys were analyzed using descriptive statistics and paired-samples t-test. RESULTS: A total of 519 participants were involved in the project. Knowledge of anti-corruption significantly increased, with 80–100% passing the criteria. Overall satisfaction was high to very high. Tangible outcomes included 29 infographic media, 12 prototype innovations, one anti-corruption course, and one student leader network. THEORETICAL/POLICY IMPLICATIONS: The STRONG Model was effective in promoting anti-corruption awareness, supporting governance and behavioral learning theories. Participatory learning, digital innovation, and leadership networks are recommended for strengthening the national anti-corruption strategy.